Central Diabetes Insipidus in Langerhans Cell Histiocytosis: A Case Report - Dya Mulya Lestari; Eka Agustia Rini (HM Publisher, 2023)
Background: Diabetes insipidus (DI) is part of a group of hereditary or acquired polyuria and polydipsia diseases. Diabetes insipidus can be caused by central and nephrogenic disorders. This study aimed to describe the etiologies, clinical symptoms, and management of central diabetes insipidus in Langerhans cell histiocytosis. Case presentation: A 4 years 4 months old boy came with excessive and frequent micturition since 9 months ago. The patient drinks 4-5 L per day and still feels thirsty. The patient had a history of Langerhans cell histiocytosis (LCH). During laboratory work-up, urine osmolarity decreased, and serum osmolarity and electrolyte were normal. The patient was diagnosed with central diabetes insipidus with Langerhans cell histiocytosis. The treatment given to the patient is desmopressin. Conclusion: Langerhans cell histiocytosis may affect any organs of the body. The long-term management of diabetes insipidus in Langerhans cell histiocytosis requires measurement to prevent dehydration and, at the same time to prevent water intoxication. The focus of management is based on the education of the patient about the importance of regulating their fluid intake according to the patient’s hydration status.